2004
DOI: 10.1242/jeb.00733
|View full text |Cite
|
Sign up to set email alerts
|

Learning, odour preference and flower foraging in moths

Abstract: Floral volatiles play a major role in plant-insect communication. We examined the influence of two volatiles, phenylacetaldehyde and α-pinene, on the innate and learnt foraging behaviour of the moth Helicoverpa armigera. In dual-choice wind tunnel tests, adult moths flew upwind towards both volatiles, with a preference for phenylacetaldehyde. When exposure to either of these volatiles was paired with a feeding stimulus (sucrose), all moths preferred the learnt odour in the preference test. This change in prefe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
100
1
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 147 publications
(105 citation statements)
references
References 35 publications
0
100
1
1
Order By: Relevance
“…The cognitive basis of pollinator attraction to floral volatiles can be innate [56] or learned [57]. The sensory preferences of insects involved in highly specialized brood-site mutualisms are expected to be innate [58,59], and may arise from mutual adaptations of the pollinators' sensory systems and floral signals. This contention is supported by the differences in electrophysiological responses to particular compounds that we observed for beetles from different populations ( figure 1d-f ).…”
Section: Discussionmentioning
confidence: 99%
“…The cognitive basis of pollinator attraction to floral volatiles can be innate [56] or learned [57]. The sensory preferences of insects involved in highly specialized brood-site mutualisms are expected to be innate [58,59], and may arise from mutual adaptations of the pollinators' sensory systems and floral signals. This contention is supported by the differences in electrophysiological responses to particular compounds that we observed for beetles from different populations ( figure 1d-f ).…”
Section: Discussionmentioning
confidence: 99%
“…In the moth Helicoverpa armigera, for instance, Cunningham et al (2004) have shown that experience-deprived adult moths raised in isolation exhibit innate preferences for phenylacetaldehyde when tested in dual-choice wind tunnel tests. Again, this preference changes rapidly if a nonpreferred volatile substance is paired with a feeding stimulus (sucrose solution).…”
Section: Selection Of Habitat Feeding and Foragingmentioning
confidence: 99%
“…Plant volatiles can attract pollinators, provide learning cues for foraging insects, serve as herbivore repellants or attractants, or attract natural enemies of herbivores (De Moraes et al 1998;Pichersky and Gershenzon 2002;Cunningham et al 2004;Ashman et al 2005;Huber et al 2005). Despite the many ways that scent influences interactions between plants and insects, we know relatively little about how herbivores and pollinators respond to the same scent volatiles.…”
Section: Introductionmentioning
confidence: 99%